DNA EXTRACTION FROM FORMALIN FIXED TISSUE USING AN ALTERNATIVE PROTOCOL (Journal of Forensic Medicine & Toxicology, 2024)
It is always a challenging task for obtaining desired amount of amplifiable DNA from formalin-fixed and non paraffin-embedded tissue sample for the purpose of human individualization, since formalin fixation of tissue samples causes fragmentation of the DNA and formation of cross linked protein-DNA complexes. The present study sought laboratories in cases related to product of conception,abandoned babies, microtomized and stained histo- pathological slides etc. needing DNA test.
Keywords: Formalin fixed tissue; DNA Extraction; de crosslinking; PCR amplification; DNA profiling